Sharp Estimates of Pochhammer’s Products - Vito Lampret (Mathematics)
Sharp, asymptotic estimates of classical and generalized rising/falling Pochhammer’s products having positive arguments are presented on the basis of Stirling’s approximation formula for the <semantics>Γ</semantics> function.